(untitled) (International Journal of Innovative Technologies in Economy, 2022)
The article discusses the role of agribusiness in the country’s economy. It also outlines strategies aimed at creating an enabling environment for small and medium-sized enterprises, increasing their competitiveness and innovation opportunities, resulting in increased incomes and employment generation, and thus achieving inclusive and sustainable economic growth. The Government of Georgia has implemented and continues to implement programs for the development of the agricultural sector in the following directions: 1. The further improvement of the legislative, institutional business environment; 2. Improving access to finance; 3. Development of competitive human capital, entrepreneurial skills and modern entrepreneurial culture; 4. Export promotion and the internationalization of small and medium-sized businesses; 5. Supporting innovations, research and development. The article discusses what damage the pandemic has caused to the country’s population and farmers. An analysis of the research results is also given, which revealed challenge facing small entrepreneurs engaged in the agricultural sector and those who are interested in agribusiness. The following training modules were conducted to address these problems: • Risk management; • The selection of marketing research methods, • Exploring new sources of funding; • Organizing marketing events; • Aspects of farming.